2007
DOI: 10.1029/2006sw000260
|View full text |Cite
|
Sign up to set email alerts
|

GPS and ionospheric scintillations

Abstract: Ionospheric scintillations are one of the earliest known effects of space weather. Caused by ionization density irregularities, scintillating signals change phase unexpectedly and vary rapidly in amplitude. GPS signals are vulnerable to ionospheric irregularities and scintillate with amplitude variations exceeding 20 dB. GPS is a weak signal system and scintillations can interrupt or degrade GPS receiver operation. For individual signals, interruption is caused by fading of the in‐phase and quadrature signals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
523
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(532 citation statements)
references
References 64 publications
6
523
0
3
Order By: Relevance
“…Given the morphology of the Earth's magnetic field, the geographic regions in which scintillations are more likely to occur are the polar and the equatorial areas, exacerbating in the low latitude regions (Kintner et al 2007). At low latitudes, the so-called ''fountain effect'', due to the interplay between E · B drift, gravity and pressure gradients, leads to an enhancement of ionization in the regions close to ±15°magnetic latitude.…”
Section: Introductionmentioning
confidence: 99%
“…Given the morphology of the Earth's magnetic field, the geographic regions in which scintillations are more likely to occur are the polar and the equatorial areas, exacerbating in the low latitude regions (Kintner et al 2007). At low latitudes, the so-called ''fountain effect'', due to the interplay between E · B drift, gravity and pressure gradients, leads to an enhancement of ionization in the regions close to ±15°magnetic latitude.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that ionospheric structures, such as the sporadic E (Es), equatorial plasma irregularities (EPIs), equatorial ionization anomaly (EIA), polar patches, and auroral blobs, can cause additional influence on the GNSS signal (e.g., Basu et al, 1980Basu et al, , 2002Crowley et al, 2000;Kintner et al, 2004Kintner et al, , 2007Yue et al, 2016). These ionospheric structures with spatial scales from hundreds of kilometers down to meters produce rapid fluctuations of the received signal phase and amplitude termed as scintillations.…”
Section: Introductionmentioning
confidence: 99%
“…In some worse cases, the signal can even be interrupted or cause navigation failure. From a global view, scintillations on GNSS are more severe and frequent at low latitudes, particularly during post-sunset hours and high solar activity years, and at high latitudes scintillations also occur but less severe in magnitude (Kintner et al, 2007). Until now, the ionospheric scintillation is still one of the most challenging problems in GNSS navigation (Basu et al, 2002;Conker et al, 2003;Dehel et al, 2004;Kintner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ionospheric irregularities can affect the propagation of trans-ionospheric radio wave signals by causing fluctuations in its amplitude and phase, called scintillations (Yeh & Liu 1982;Kintner et al 2007). In the case of the Global Positioning System (GPS), scintillations may reduce the accuracy of the pseudo-range and carrier phase measurements.…”
Section: Introductionmentioning
confidence: 99%